2007
DOI: 10.1186/1471-2377-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of depression, disability, and family caregiver attitudes to the quality of life of Kuwaiti persons with multiple sclerosis: a controlled study

Abstract: Background: Assessment of subjective quality of life (QOL) of persons with multiple sclerosis (MS) could facilitate the detection of psychosocial aspects of disease that may otherwise go unrecognized. The objectives of the study were to (i) compare the QOL ratings of relapsing remitting (RRMS) and progressive (PMS) types of MS with those of a general population group and the impression of their family caregivers; and (ii) assess the association of demographic, clinical, treatment, depression, and caregiver var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…Participants were in stable clinical condition and could independently give consent to participate in the study 7. In this culture, female patients are, as a rule, accompanied to hospital by family members who live with them 12. Consent was also obtained from the family members, but the patients were interviewed privately in one of the clinic rooms.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were in stable clinical condition and could independently give consent to participate in the study 7. In this culture, female patients are, as a rule, accompanied to hospital by family members who live with them 12. Consent was also obtained from the family members, but the patients were interviewed privately in one of the clinic rooms.…”
Section: Methodsmentioning
confidence: 99%
“…These ICF categories are known to correlate with other variables, e.g. health-related quality of life or general health [18][19][20][21][22][23][24][25]. Furthermore, these aspects are perhaps intermittent variables and interfere with functioning in pwMS, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…The studies contained results from 10 countries across five continents: Australia [28,31], Brazil [30,34,35], Czech Republic [35], Germany [35], Republic of Korea [32], Kuwait [25], Spain [35], Sudan [26,27], Turkey [35], and the United Kingdom [35].…”
Section: Participantsmentioning
confidence: 99%
“…We grouped persons into the three broad categories of (1) mental health (n 5 604): schizophrenia, major affective disorder, neurosis, bipolar disorder, and psychosis [26,31,32]; (2) intellectual disability (n 5 614): mild learning disability [35]; (3) Physical health (n 5 762): cancer, type 2 diabetes, multiple sclerosis, and infertility [25,27,28,30,34]. As Awadalla et al [26] reported three groups of persons with mental health problems, we analyzed these separately.…”
Section: Personsmentioning
confidence: 99%